Experimental study on radioactive waste immobilization in low-temperature magnesium-potassium phosphate ceramic matrix - Sayenko, S.Yu.; Shkuropatenko, V.A.; Pylypenko, A.V.; Zykova, A.V.; Karsim, S.A.; Andrieieva, V.V.; Moshta, S.V. (Вопросы атомной науки и техники, 2020)
Results of the studies carried out in NSC KIPT on application of magnesium-potassium phosphate ceramic matrices for immobilization of cesium, clinoptilolite with a cesium and solidified simulators of highly-active waste with high salt content are presented. The high radiation stability and corrosion resistance of the magnesiumpotassium phosphate ceramic matrices to leaching of radionuclide simulators, as well as basic components of solidified ceramic compounds were determined. It was shown that magnesium-potassium phosphate matrices for the solidification of liquid radioactive wastes of low and middle activity level, including waste with increased salt content, can be used in Ukrainian NPPs. Представлені результати виконаних у ННЦ ХФТІ робіт по застосуванню калій-магній-фосфатних керамічних матриць для іммобілізації цезію, кліноптилоліту з цезієм та отвердження імітаторів високосольових високоактивних відходів. Встановлена висока радіаційна та корозійна стійкісті отриманих матриць до вилуговування імітаторів радіонуклідів та основних компонентів твердих керамічних компаундів. Показано, що калій-магній-фосфатна матриця може бути використана для отвердження рідких радіоактивних відходів АЕС України низького та середнього рівнів активності, у тому числі зі збільшеним солевмістом. Представлены результаты выполненных ННЦ ХФТИ работ по применению калий-магний-фосфатных керамических матриц для иммобилизации цезия, клиноптилолита с цезием и отверждения имитаторов высокосолевых высокоактивных отходов. Установлена высокая радиационная и коррозионная стойкости полученных матриц к выщелачиванию имитаторов радионуклидов и основных компонентов твердых керамических компаундов. Показано, что калий-магний-фосфатная матрица может быть использована для отверждения жидких радиоактивных отходов АЭС Украины низкого и среднего уровней активности, в том числе с увеличенным солесодержанием.